Effects of acitretin on semen quality and reproductive hormone levels in patients with psoriasis vulgaris - Hui Liu; Jie Li; Li Yu (Wolters Kluwer Medknow Publications, 2017)
Background: The aim of this study was to investigate the effect of different doses of acitretin (ACI) on the main parameters of semen, sperm morphology, and reproductive hormone levels in patients with psoriasis vulgaris. Methods: The main parameters of semen and the sperm morphology of 31 psoriatic patients were analyzed before and after treatment with different doses of ACI, and the changes in reproductive hormone levels were measured and compared with those of 14 healthy control individuals. Results: At treatment doses of 20 mg/d (n = 15) and 30 mg/d (n = 16) of ACI, the semen volume, sperm motility, viability, concentration, and normal appearance percentage, and the serum reproductive hormone levels in the psoriatic patients showed no significant difference from those in healthy control individuals (n = 14) after 1 month and 3 months of treatment, as well as after withdrawing the treatment for 3 months (p > 0.05). Conclusion: Different doses of ACI did not significantly affect semen quality in psoriatic patients at different treatment stages.